Homeotic Complex (Hox) gene regulation and homeosis in the mesoderm of the Drosophila melanogaster embryo: the roles of signal transduction and cell autonomous regulation. - Miller, D.F.B.; Holtzman, S.L.; Kalkbrenner, A.; Kaufman, T.C. (Mechanisms of Development, 2001)
In this paper we evaluate homeosis and Homeotic Complex (Hox) regulatory hierarchies in the somatic and visceral mesoderm. We demonstrate that both Hox control of signal transduction and cell autonomous regulation are critical for establishing normal Hox expression patterns and the specification of segmental identity and morphology. We present data identifying novel regulatory interactions associated with the segmental register shift in Hox expression domains between the epidermis/somatic mesoderm and visceral mesoderm. A proposed mechanism for the gap between the expression domains of Sex combs reduced (Scr) and Antennapedia (Antp) in the visceral mesoderm is provided. Previously, Hox gene interactions have been shown to occur on multiple levels: direct cross-regulation, competition for binding sites at downstream targets and through indirect feedback involving signal transduction. We find that extrinsic specification of cell fate by signaling can be overridden by Hox protein expression in mesodermal cells and propose the term autonomic dominance for this phenomenon.